Molecular And Neurophysiological Commentaries On The Main Issue Of Suicide - Vardanyan, K. E.; Tigranyan, T. G.; Ghazaryan, A. A. (Մանկավարժ հրատ․)
The suicide phenomenon is considered within anthropological, psychological, philosophical, ecological, and socio-psychological science contexts. However, the most modern approach is to the brain's processes at molecular level, especially, with special reference to the dopamine and particularizing the changes associated with serotonin mediators, combining them with different manifestations of individual aggressiveness, and the peculiarities of XYY syndrome. The present research covers the reasons of suicide within molecular realm, as well as neuropsychological and psychological theories. The suicide has different manifestations: it is socio-psychological destructive disadaptation during which some marginal psychological symptoms are noticed in patient’s conduct: narrowness mental sensitive enhanced with depression and self-aggression, memory, thinking and self-awareness destruction which is observed, in fact, in pre-suicide and during which the suicidal thoughts transfer to suicidal decision. Within the complex of asocial behavior among the teenagers, the suicide has its special role acting as a kind of deflective behavior. Ինքնասպանություն երևույթը բնութագրվում է մարդաբանական, հոգեբանական, փիլիսոփայական, էկոլոգիական, սոցիալ-հոգեբանական գիտությունների համատեքստում: Սակայն առավել արդիական մոտեցում է մոլեկուլային մակարդակով գլխուղեղում ընթացող գործընթացները, հատկապես դոֆամին, սերոտոնին միջնորդանյութերի հետ կապված փոփոխությունները, դրանց զուգակցումը անձի ագրեսիվության տարբեր դրսևորումների հետ, XYY համախտանիշի դրսևորման առանձնահատկությունները: Աշխատանքում ուշադրություն է դարձվում նաև B խմբին պատկանող բիոտին վիտամինի պակասի հետ կապված ինքնասպանության նկատմամբ հակմանը: Մարդկանց և կապիկների օրգանիզմում հայտնաբերվել է Mir-1202 մոլեկուլը: Որքան փոքր է այդպիսի մոլեկուլի խտությունը, այնքան մեծ է դեպրեսիայով տառապելու և աուտոագրեսիա իրականացնելու հավանականությունը: Явление суицида характеризуется в контексте антропологических, психологических, философских, экологических, социально-психологических наук. Но наиболее современными представлениями являются процессы, происходящие в мозге на молекулярном уровне, в особенности модификации, связанные с медиаторами дофамин, серотонин, их сочетание с различными проявлениями агрессивности человека, особенности проявления синдрома XYY. В работе внимание уделяется также склонности к самоубийству тех людей у которых дефицит витамина ˝биотин˝ (группа B). ˝Молекула Мир-1202˝ была обнаружена у людей и обезьян. Чем меньше концентрация такой молекулы, тем больше вероятность депрессии и совершения аутоагрессии.
Keywords: Physiology